The Effect of Public Accounting Firm Size, Managerial Ownership, and Company Size on Financial Statement Integrity - Wahyu Ningrum, Wulan; Monica Olivia (Future Science, 2024)
Financial statements must be presented accurately and unbiasedly so that they can be used as a basis for decision making by stakeholders. Therefore, financial statements must have high integrity. Based on the global context and differences in the results of previous studies, this study aims to replicate previous research using the latest data. This study has a specific objective to determine whether the size of the Public Accounting Firm, managerial ownership and company size, can affect the integrity of financial statements in consumer goods companies during 2020-2022. This study uses multiple regression analysis, with descriptive statistical testing. Based on empirical evidence, the results show that the size of the public accounting firm and company size have a positive effect on the integrity of financial statements. Meanwhile, managerial ownership has a negative effect on the integrity of financial statements.